Rättslig operationalisering av företags samhällsansvar : Särskilt om avtalsrätt, köprätt, konsumentköprätt, marknadsföringsrätt och aktiebolagsrätt - Halje, Lovisa (Uppsala universitet, 2022)
The main objective of this thesis is to explore and describe the possibilities for legal operationalization of CSR in contract law, sales law and consumer sales law, marketing law and company law. A supplementary aim is to identify regulation on and illustrate the regulatory context of CSR. The illustration provides a background and a framework for the main objective of the study, as well as confirms the legal relevance of CSR. Legal operationalization of CSR requires that CSR is anchored in law and that there are mechanisms for enforcement available. In contract law, CSR is legally anchored when a CSR condition follows from a contract. In a Swedish sales law context, legal anchoring takes place when a buyer’s expectation regarding CSR is not met and this is considered a defect, fel. From a marketing law point of view, the possibilities to consider a CSR statement an unfair commercial practice are relevant. In a company law context, CSR is legally anchored when included in the articles of association, in an instruction from the general meeting or the board, in the board’s internal guidelines or in the remuneration guidelines of the company. In all, contract parties, shareholders and the board are “strong” legal subjects, in that they are able to proactively formulate and anchor CSR norms in law. In company law, the understanding of the company’s interest and purpose, as well as the business case for CSR and the understanding of profit create borders within which the company law operationalization of CSR functions. Sales law and marketing law offer retroactive tools to market actors. The possibilities to anchor CSR in marketing law are vast, whereas the applicability of the sales law rules to a large extent is dependent on the connection between the (failed) CSR expectation and the sold goods. The remedies in the explored areas of law typically do not protect the CSR interest in question directly.
URN: urn:nbn:se:uu:diva-450030 OAI: oai:DiVA.org:uu-450030 DiVA, id: diva2:1583825
Keywords: Aktiebolagsrätt; Avtalsrätt; CSR; Company law; Contract law; Corporate Social Responsibility; Corporate sustainability; Företags samhällsansvar; Förrättsligande; Hållbarhet; Hållbart företagande; Juridification; Konsumentköprätt; Köprätt; Legal operationalization; Legalization; Marketing law; Marknadsföringsrätt; Private law; Privaträtt; Rättslig operationalisering; Sales law; Sustainability

Institutionella samspel : Om möten mellan en kommersiell och en ideell logik - Kvarnstrom, Emilia (Företagsekonomiska institutionen, Uppsala universitet, 2016)
Institutional logics create order and stability. They organize interaction and prescribe how we should behave towards each other. Such logics have generally been regarded as exclusive, in the sense that an organizational field is always guided by a single institutional logic. If there are two or more institutional logics in one setting at the same time this will create conflicting demands and contradictions. So how do organizations and individuals that act in these settings, where different institutional logics do meet, cope with the conflicting demands? This question is researched by studying actors who organize partnerships between corporations and non-profit organizations. Institutional logics have typically been studied at field level. My study follows a more recent literature strand focusing on individuals and their way of coping with conflicting institutional logics. In this thesis, interviews, text analysis and observations are used. The interviews were conducted with CSR managers of corporations, managers of corporate partners at non-profit organizations, CSR consultants, and project managers of intermediary organizations. These actors are working in an environment where conflicting institutional logics are played out. Using a narrative approach it is shown how these actors are aware of their institutional environment and its conflicts which requires them to constantly act as translators. The study shows that the actors organize an interplay between a market-logic and a social-welfare logic by bringing together the logics and establishing limits to what extent logics can be mixed. Thus, the actors can be understood as bilingual, rather than hybrids. Furthermore, it is argued that a narrative approach provides the possibility to understand institutional logics in empirical contexts as more present and visible than they are usually considered to be. The study concludes that bilingual actors balance conflicting demands and negotiate requirements set by institutional logics in their day-to-day work. Settings where institutional logics meet can hence be understood as both a contradiction and an ongoing interplay.
Series Doctoral thesis / Företagsekonomiska institutionen, Uppsala universitet, ISSN 1103-8454 ; 180 Identifiers URN: urn:nbn:se:uu:diva-304749 OAI: oai:DiVA.org:uu-304749 DiVA, id: diva2:1033784
Keywords: Actor; Cross-sectoral partnerships; Hybrid organization; Institutional logics; Institutional theory; Narrative; Partnerships